Therapeutic efficacy of matrix metalloproteinase-12 suppression on neurological recovery after ischemic stroke: Optimal treatment timing and duration - Siva Reddy Challa; Siva Reddy Challa; Koteswara Rao Nalamolu; Casimir A. Fornal; Billy C. Wang; Billy C. Wang; Billy C. Wang; Ryan C. Martin; Elsa A. Olson; Ammar L. Ujjainwala; David M. Pinson; Jeffrey D. Klopfenstein; et al. (Frontiers in Neuroscience, 2022)
We recently showed that the post-ischemic induction of matrix metalloproteinase-12 (MMP-12) in the brain degrades tight junction proteins, increases MMP-9 and TNFα expression, and contributes to the blood-brain barrier (BBB) disruption, apoptosis, demyelination, and infarct volume development. The objectives of this study were to (1) determine the effect of MMP-12 suppression by shRNA-mediated gene silencing on neurological/functional recovery, (2) establish the optimal timing of MMP-12shRNA treatment that provides maximum therapeutic benefit, (3) compare the effectiveness of acute versus chronic MMP-12 suppression, and (4) evaluate potential sex-related differences in treatment outcomes. Young male and female Sprague-Dawley rats were subjected to transient middle cerebral artery occlusion and reperfusion. Cohorts of rats were administered either MMP-12shRNA or scrambled shRNA sequence (control) expressing plasmids (1 mg/kg; i.v.) formulated as nanoparticles. At designated time points after reperfusion, rats from various groups were subjected to a battery of neurological tests to assess their reflex, balance, sensory, and motor functions. Suppression of MMP-12 promoted the neurological recovery of stroke-induced male and female rats, although the effect was less apparent in females. Immediate treatment after reperfusion resulted in a better recovery of sensory and motor function than delayed treatments. Chronic MMP-12 suppression neither enhanced nor diminished the therapeutic effects of acute MMP-12 suppression, indicating that a single dose of plasmid may be sufficient. We conclude that suppressing MMP-12 after an ischemic stroke is a promising therapeutic strategy for promoting the recovery of neurological function.